Nuestras vías de comunicación y la corriente de "El niño". - Erazo, Anta (Revista Universidad de Guayaquil, 1997)
When our wise professor of Transportation Systems at the Faculty of Mathematical and Physical Sciences of the University of Guayaquil, Engineer Pedro Manrique Acevedo, taught us about roads and railways, he told us that when building these structures, civil engineers must take great care in the design and construction of what are known as “engineering structures.” These are the names given to bridges; drainage works; longitudinal ditches; culverts; retaining structures: masonry and reinforced concrete walls; defense walls to channel river water that could cause damage or undermining of the bases of walls and bridge piers; curve defenses; and signaling works.